Sharia-Based Regional Regulations in the Indonesian National Law System - Abbas, Syahrizal; Murziqin, Ramzi (SCAD Independent, 2021)
This study aimed to explain the existence of sharia-based regional regulations and discuss the form of legal system regulation of sharia-based regional regulations in Indonesia. After the reformation, changes in the legal system in Indonesia began, especially the change from a centralized pattern to a decentralized one and the granting of regional autonomy authority, this was marked by the issuance of regional regulations based on the needs of each region. The next problem is the emergence of the desire to establish sharia-based regional regulations such as in Aceh, South Sulawesi, and West Java which invites legal discourse on the legal system in Indonesia. This study used a qualitative method with a normative legal approach. The subjects of this study were the namely elements of the Central and Regional Government, and Members of the DPRD. In addition, information was also collected from scholars, academics, and legal practitioners. The research procedure was carried out in four steps: observation, in-depth interviews, and documentation. The data were analyzed using an inductive model. The research findings showed that; first, the implementation of post-reform Islamic Shari'a cannot be separated from the increase in democratic life in Indonesia. Second, the application of Islamic Shari'a is the desire of the community as the foundation and order of social, national, and religious life. Third, the application of sharia-based regional regulations in addition to being elite political capital is also part of increasing identity and cultural revival and social life of the community.